2017
DOI: 10.1186/s12941-017-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and virulence characterization of Staphylococcus aureus and coagulase-negative staphylococci from imported beef meat

Abstract: BackgroundThe objectives of this study were to characterize the diversity and magnitude of antimicrobial resistance among Staphylococcus species recovered from imported beef meat sold in the Egyptian market and the potential mechanisms underlying the antimicrobial resistance phenotypes including harboring of resistance genes (mecA, cfr, gyrA, gyrB, and grlA) and biofilm formation.ResultsThe resistance gene mecA was detected in 50% of methicillin-resistant non-Staphylococcus aureus isolates (4/8). Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 47 publications
3
48
1
6
Order By: Relevance
“…Momtaz, Dehkordi, Rahimi, Ezadi, et al () and Momtaz, Dehkordi, Rahimi, Asgarifar, et al () indicated that S. aureus strains isolated from chicken meat samples had high levels of resistance against streptomycin (31.70%), tetracycline (97.56%), trimethoprim (31.70%), enrofloxacin (28.04%), gentamicin (29.26%), sulfamethoxazole (31.70%), cephalothin (17.07%), ampicillin (26.82%), chloramphenicol (20.73%), and methicillin (75.60%) antibiotics which were similar to our findings. Osman et al () reported that S. aureus strains of food samples collected from Egypt had high prevalence of resistance against ampicillin (26.08%), methicillin (34.78%), erythromycin (26.08%), chloramphenicol (4.34%), ciprofloxacin (30.43%), vancomycin (39.13%), and tetracycline (26.08%) antibiotics. They showed that 96% of strains were resistant to penicillin and trimethoprim–sulfamethoxazole antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Momtaz, Dehkordi, Rahimi, Ezadi, et al () and Momtaz, Dehkordi, Rahimi, Asgarifar, et al () indicated that S. aureus strains isolated from chicken meat samples had high levels of resistance against streptomycin (31.70%), tetracycline (97.56%), trimethoprim (31.70%), enrofloxacin (28.04%), gentamicin (29.26%), sulfamethoxazole (31.70%), cephalothin (17.07%), ampicillin (26.82%), chloramphenicol (20.73%), and methicillin (75.60%) antibiotics which were similar to our findings. Osman et al () reported that S. aureus strains of food samples collected from Egypt had high prevalence of resistance against ampicillin (26.08%), methicillin (34.78%), erythromycin (26.08%), chloramphenicol (4.34%), ciprofloxacin (30.43%), vancomycin (39.13%), and tetracycline (26.08%) antibiotics. They showed that 96% of strains were resistant to penicillin and trimethoprim–sulfamethoxazole antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Such discrepancy when interpreting the results may be possible since the test itself was not originally designed for investigating P. aeruginosa isolates as reported by Freeman et al [21]. In this investigation, according to Osman et al [48], isolates that produced black/rough colonies were verified as strong biofilmforming, while isolates producing red/smooth colonies were described as non-biofilm formers. The smooth black and dry red colonies were respected as indefinite findings.…”
Section: Discussionmentioning
confidence: 81%
“…Our results showed that the frequency of hemolytic agent genes of hla, hlb, hld were higher in cefoxitin resistant isolates compared to susceptible ones. [41][42][43].…”
Section: Discussionmentioning
confidence: 99%